2023
DOI: 10.26599/bsa.2023.9050001
|View full text |Cite
|
Sign up to set email alerts
|

BK channels in microglia

Abstract: Large-conductance calcium-and voltage-dependent potassium (BK) channels are ubiquitously expressed in mammalian cells and participate in various physiological and pathological processes such as neurotransmission and cerebral ischemia. BK channels comprise up to four pore-forming α subunits and zero to four accessory subunits. Although microglial BK currents were initially recorded 27 years ago, their roles have long been elusive. Studies have demonstrated that BK channels modulate the activation, phagocytosis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Studies have demonstrated that BK channels modulate the activation, phagocytosis, and probably migration of microglia and have associated microglial BK channels with many neurological diseases, including neuropathic pain and stroke. Dr. Sun [2] summarizes the available information regarding the biophysical, functional, and pathological aspects of microglial BK channels and discusses future directions of research into these channels.…”
mentioning
confidence: 99%
“…Studies have demonstrated that BK channels modulate the activation, phagocytosis, and probably migration of microglia and have associated microglial BK channels with many neurological diseases, including neuropathic pain and stroke. Dr. Sun [2] summarizes the available information regarding the biophysical, functional, and pathological aspects of microglial BK channels and discusses future directions of research into these channels.…”
mentioning
confidence: 99%